POLLEN, STARCH, PROTEIN RESIDUE AND ORGANIC RESIDUE (FTIR) ANALYSIS OF ARTIFACTS FROM SITE 24HL1085, NORTH-CENTRAL MONTANA - Cummings, Linda Scott; Yost, Chad (2008)
Two possible groundstone tools and three fire-cracked rocks (FCR) were submitted for pollen, starch grain, protein residue and/or organic residue (FTIR) analysis from site 24HL1085, located in the Bear’s Paw Mountains of north-central Montana. This site is situated on a low and narrow terrace overlooking the East Fork of Beaver Creek in Hill County, and the samples submitted are part of on-going work in the area. The goal of the current analysis is to determine what animals and plants might have been processed using these tools or cooked in the thermal feature(s) associated with the fire-cracked rock.